Analisis Balanced Scorecard Sebagai Alat Pengukur Kinerja PT. Bank NegaraI Indonesia Syariah Cabang Makassar - Hermin Andi Magga; Roswiyanti Roswiyanti (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
This study aims to determine the influence of financial perspective, customer perspective, internal business process perspective, and growth and learning perspective on the performance of PT. Bank Negara Indonesia Syariah Branch Makassar. This research method is quantitative and qualitative. Population in the study were employees and customers of PT.BNI Syariah Makassar Branch. Data collection techniques using questionnaires. Data collected and processed using SPSS. Based on the results obtained financial perspective variables (X1) amounted to 2.241 with R persial 0.030, (X2) amounted to 3.879 with r persial 0.000 , Internal business (X3) amounted to 2.391 with r persial 0.021 with GIS 0.05, growth and learning (X4) amounted to -2.412 with r persial 0.020.